2008
DOI: 10.1029/2008gl033719
|View full text |Cite
|
Sign up to set email alerts
|

Higher tropical SSTs strengthen the tropical upwelling via deep convection

Abstract: [1] Recent observations show a distinct cooling of the tropical lower stratosphere, and chemistry-climate models (CCMs) suggest a link to a strengthening tropical upwelling, arguably related to increases in greenhouse gas concentrations from anthropogenic activity. The present study explores the strengthening of tropical upwelling by comparing ensemble realisations of two different transient scenarios with the CCM E39/C. Both scenarios share the same boundary conditions, including concentrations of ozone-deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
64
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 25 publications
15
64
0
1
Order By: Relevance
“…The SST increases in runs E2 to E4 all caused a decrease in the stratospheric mean age-of-air, implying that SST increases tend to accelerate upward transport in the stratosphere. This result is consistent with the results in previous studies (Deckert and Dameris, 2008;Shu et al, 2011). Overall, the mean age-of-air in the upper stratosphere was youngest in E4 and the oldest in E3 (Fig.…”
Section: Effects Of Sst Changes On the Bdc And Tropopausesupporting
confidence: 83%
See 1 more Smart Citation
“…The SST increases in runs E2 to E4 all caused a decrease in the stratospheric mean age-of-air, implying that SST increases tend to accelerate upward transport in the stratosphere. This result is consistent with the results in previous studies (Deckert and Dameris, 2008;Shu et al, 2011). Overall, the mean age-of-air in the upper stratosphere was youngest in E4 and the oldest in E3 (Fig.…”
Section: Effects Of Sst Changes On the Bdc And Tropopausesupporting
confidence: 83%
“…Subsequently, some studies have argued that BDC is mainly affected by SST changes and that radiative effects of GHGs are less important than the SST changes in modulating tropical upwelling (Xie et al, 2008). Deckert and Dameris (2008) suggested that warmer tropical SSTs will strengthen the lower-stratospheric BDC in the tropics in the summer hemisphere via enhancing deep-convective generation of upward propagating quasi-stationary eddies. Some other studies have shown that SST changes can modulate BDC by changing propagation properties of synoptic and planetary-scale waves both in the troposphere and stratosphere (e.g., Butchart et al, 2006Butchart et al, , 2010Shepherd and McLandress, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…2c and d shows that the SST/SI weaken the westerly wind over the middle and high latitudes of the SH and NH and substantially strengthens both subtropical jets extending their upper flanks in a vertical direction. Such changes of the subtropical jets enhance penetration and dissipation of waves in the lower stratosphere leading to an intensification of the BDC (Rind et al, 2002;Deckert and Dameris, 2008;Garcia and Randel, 2008;Calvo and Garcia, 2009;McLandress and Shepherd, 2009;Shepherd and McLandress, 2011). Additional warming of the polar lower stratosphere caused by the ODS forcing (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The drop in tropical tropopause temperature and reduced entry of water vapor into the stratosphere at the end of 2000 appears to be connected to an enhanced rate of tropical upwelling [58,59] and associated changes in eddy wave driving [61]. Moreover, there is still no agreement about the cause-effect-chain for the strengthening of tropical upwelling near the tropical tropopause; both tropical SST changes [62] and changes in high-latitude wave forcing [63] have been suggested. Another hint for an insufficient understanding of atmospheric processes determining the variability of tropopause temperature and not least the water vapor content in the lower stratosphere is that by now, no CCM has simulated a similar sharp decrease of tropopause temperature or water vapor concentration at any specific period during multi-decadal simulations.…”
Section: Water Vapor In the Stratospherementioning
confidence: 95%